A comparative analysis of contemporary integrated java environments - Kaczorowski, Cezary (Journal of Computer Sciences Institute, 2023)
The purpose of this study was to compare three of the most popular Java development environments: IntelliJ IDEA, Netbeans, and Eclipse, in order to identify the best one for specific user archetypes. Using a program specially designed for this task, the execution time was measured, as well as the CPU and RAM usage during the execution of the program on each environment. The obtained data was collected and processed accordingly. Additionally, the environments were compared in a number of ways, including features that distinguish them from each other, ease learnability for a new user or support from the developers. The study concluded with IntelliJ IDEA being the best environment for all of the considered archetypes.